STUDENTS' MATHEMATICAL REASONING ABILITY IN LEARNING - Herdiyanus Warae; Putriani Ndruru; Restu Dohude (Afore : Jurnal Pendidikan Matematika, 2022)
The research used a qualitative research approach with a descriptive research type. The informants in this study were class X SMK in Lolomaya Village. Data collection carried out in this study were tests and interviews. The test is used to determine students' mathematical reasoning abilities by using 5 item description questions that contain reasoning. Interviews were conducted to find out in depth students' mathematical reasoning abilities in solving mathematical problems which were attended by 6 students out of 10 students who were selected based on student abilities, namely 2 students with high abilities, 2 students with moderate abilities and 2 students with low abilities. The results of this study are (1) high ability students fulfill the indicators by making conjectures; perform mathematical manipulations; compiling evidence; draw conclusions from a statement and check the validity of an argument. (2) students who are capable of fulfilling the indicators submit conjectures and check the validity of an argument. (3) students who have low ability to meet the indicators submit conjectures